Meningkatkan Hasil Belajar Shooting Pada Permainan Bola Basket Melalui Modifikasi Bola (Department of Physical Education, Sport, Health and Recreation, 2015)
This study uses classroom action research (CAR). The subjects of this study were fifth-grade students of SD Negeri 02 Dadirejo Pekalongan, while the object of the study using a modified method of the ball. students used were fifth grade students of SD Negeri 02 Dadirejo Pekalongan, in the 2nd half of the school year 2013/2014, while the number of students 32 children consisted of 17 sons and 15 daughters Based on the results of this research that has been done there is an increase in student learning outcomes from the initial condition, cycle 1 and cycle 2, both from an increase in the average value of learning and the value of a basketball shooting mastery of learning outcomes. Average cycle 1 was 73.35 and the average cycle 2 was 76.30. So the increase of cycle 1 to cycle 2 by 2.95.